The clinical effectiveness and cost-effectiveness of treat-to-target strategies in rheumatoid arthritis: a systematic review and cost-effectiveness analysis - Allan Wailoo (Health Technology Assessment, 2017)
Background: Treat to target (TTT) is a broad concept for treating patients with rheumatoid arthritis (RA). It involves setting a treatment target, usually remission or low disease activity (LDA). This is often combined with frequent patient assessment and intensive and rapidly adjusted drug treatment, sometimes based on a formal protocol. Objective: To investigate the clinical effectiveness and cost-effectiveness of TTT compared with routine care. Data sources: Databases including EMBASE and MEDLINE were searched from 2008 to August 2016. Review methods: A systematic review of clinical effectiveness was conducted. Studies were grouped according to comparisons made: (1) TTT compared with usual care, (2) different targets and (3) different treatment protocols. Trials were subgrouped by early or established disease populations. Study heterogeneity precluded meta-analyses. Narrative synthesis was undertaken for the first two comparisons, but was not feasible for the third. A systematic review of cost-effectiveness was also undertaken. No model was constructed as a result of the heterogeneity among studies identified in the clinical effectiveness review. Instead, conclusions were drawn on the cost-effectiveness of TTT from papers relating to these studies. Results: Sixteen clinical effectiveness studies were included. They differed in terms of treatment target, treatment protocol (where one existed) and patient visit frequency. For several outcomes, mixed results or evidence of no difference between TTT and conventional care was found. In early disease, two studies found that TTT resulted in favourable remission rates, although the findings of one study were not statistically significant. In established disease, two studies showed that TTT may be beneficial in terms of LDA at 6 months, although, again, in one case the finding was not statistically significant. The TICORA (TIght COntrol for RA) trial found evidence of lower remission rates for TTT in a mixed population. Two studies reported cost-effectiveness: in one, TTT dominated usual care; in the other, step-up combination treatments were shown to be cost-effective. In 5 of the 16 studies included the clinical effectiveness review, no cost-effectiveness conclusion could be reached, and in one study no conclusion could be drawn in the case of patients denoted low risk. In the remaining 10 studies, and among patients denoted high risk in one study, cost-effectiveness was inferred. In most cases TTT is likely to be cost-effective, except where biological treatment in early disease is used initially. No conclusions could be drawn for established disease. Limitations: TTT refers not to a single concept, but to a range of broad approaches. Evidence reflects this. Studies exhibit substantial heterogeneity, which hinders evidence synthesis. Many included studies are at risk of bias. Future work: Future studies comparing TTT with usual care must link to existing evidence. A consistent definition of remission in studies is required. There may be value in studies to establish the importance of different elements of TTT (the setting of a target, the intensive use of drug treatments and protocols pertaining to those drugs and the frequent assessment of patients). Conclusion: In early RA and studies of mixed early and established RA populations, evidence suggests that TTT improves remission rates. In established disease, TTT may lead to improved rates of LDA. It remains unclear which element(s) of TTT (the target, treatment protocols or increased frequency of patient visits) drive these outcomes. Future trials comparing TTT with usual care and/or different TTT targets should use outcomes comparable with existing literature. Remission, defined in a consistent manner, should be the target of choice of future studies. Study registration: This study is registered as PROSPERO CRD42015017336. Funding: The National Institute for Health Research Health Technology Assessment programme.